China's new nationalism : pride, politics, and diplomacy - Gries, Peter Hays, 1967- (University of California Press, 2004)
At a time when the direction of China's foreign and domestic policies have profound ramifications worldwide, Gries offers a rare, in-depth look at the nature of China's new nationalism particularly as it involves Sino-American and Sino-Japanese relations.
Keywords: Nationalism -- China.; Anti-Americanism -- China.; Japan -- Foreign public opinion, Chinese.; Public opinion -- China.; Nationalisme -- Chine.; Antiaméricanisme -- Chine.; Opinion publique -- Chine.; Japon -- Opinion publique chinoise.; POLITICAL SCIENCE -- Political Ideologies -- Nationalism.; HISTORY -- Asia -- General.; Anti-Americanism; Nationalism; Public opinion; Public opinion, Chinese; China; Japan; Antiamerikanismus; Nationalismus; Nationalisme.; Publieke opinie.; Antiaméricanisme.; Opinion publique chinoise.; Opinion publique étrangère.; Politique étrangère.; Chine.; États-Unis.; United States -- Foreign opinion -- China.; Electronic book.